Upaya Mengembangkan Kreativitas Berwirausaha Peserta Pelatihan Tata Boga di Lkp Ghea Kota Serang - Jilianti Jilianti; Tika Santika; Uum Suminar (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the implementation and results of the culinary arts training in developing the entrepreneurial creativity of the trainees at LKP Ghea Serang City. In this study using a qualitative approach with a descriptive method. Meanwhile, the subjects in this study were a manager, an educator and three students who were randomly selected. The data collection techniques using observation, interviews and documentation. After the data was obtained, the data were analyzed using several stages, namely (1) data collection, (2) data reduction, (3) data presentation, and (4) conclusions and data verification. The result is that the implementation of culinary training at LKP Ghea Serang City was carried out for approximately 1 month using lecture, practice, question and answer methods, and direct guidance. For the percentage of training 70% practice and 30%. The results of the implementation of the culinary arts training in developing the entrepreneurial creativity of the trainees at LKP Ghea Serang City were considered quite successful, where the learning residents were able to develop knowledge and skills starting from the achievements obtained by the trainees to help the family economy through a culinary training program. the ability of participants after graduating from catering training is adequate and confident in their abilities so that they can be confident to work or open their own businesses